Motorbike racing - Norman, Tony. (Milwaukee, Wis. : Gareth Stevens Pub., 2006)
Text and photographs describe five different types of motorbike racing, mechanical and safety equipment for each, and true stories of extreme racers.
Includes index.
6.5
3-6
Keywords: Motorcycles, Racing -- Juvenile literature; Motorcycles, Racing; Motorcycles